Schuldenbremse 2020: Große Unterschiede beim Konsolidierungsbedarf der Länder - Ingolf Deubel; Jürgen Hamker; Dominik Rumpf; Dan Stegarescu (Wirtschaftsdienst, 2015)
Die Bundesländer müssen bis 2020 ihre Haushalte ausgleichen und danach die Schuldenbremse einhalten. Aufgrund der erwarteten günstigen Rahmenbedingungen ist diese Vorgabe für die meisten Bundesländer moderat zu bewältigen. Sie können sogar Ausgabenzuwächse einplanen. Allerdings zeigen die Berechnungen auch, dass einzelne Länder vor beträchlichten Herausforderungen stehen. – – This article examines the scope for expenditure of each German federal state (including local governments) to achieve a balanced budget in 2020 when the debt brake fully enters into force. After deducting interest and pension burden, a major group of states could afford marked annual increases vis-à-vis 2013. Heavily indebted Bremen could raise expenditure only slightly, whereas Saarland would have to reduce it even given lower interest rate and pension increase assumptions. Some East German states also face major challenges despite 2013 budget surpluses, as special financial assistance will be phased out. Figures adjusted for price changes indicate needs for cuts in several states.
Keywords: H68; H72; H74; 330; Haushaltskonsolidierung; Länderfinanzen; Deutschland